Here is another method to solve a system of linear equations: Solve one of the equations for one of the variables, and substitute the result into the other equations.Repeat this process until you run out of variables orequations. Consider the example discussed on page 2: | x + 2 y + 3 z = 39 x + 3 y + 2 z = 34 3 x + 2 y + z = 26 | . We can solve the first equation for x: x = 39 − 2 y − 3 z . Then we substitute this equation into the other equations: | ( 39 − 2 y − 3 z ) + 3 y + 2 z = 34 3 ( 39 − 2 y − 3 z ) + 2 y + z = 26 | . We can simplify: | y − z = − 5 − 4 y − 8 z = − 91 | . Now, y = z − 5 , so that − 4 ( z − 5 ) − 8 z = − 91 , or − 12 z = − 111 . We find that z = 111 12 = 9.25 . Then y = z − 5 = 4.25 and x = 39 − 2 y − 3 z = 2.75 . Explain why this method is essentially the same as the method discussed in this section; only the bookkeeping is different.
Here is another method to solve a system of linear equations: Solve one of the equations for one of the variables, and substitute the result into the other equations.Repeat this process until you run out of variables orequations. Consider the example discussed on page 2: | x + 2 y + 3 z = 39 x + 3 y + 2 z = 34 3 x + 2 y + z = 26 | . We can solve the first equation for x: x = 39 − 2 y − 3 z . Then we substitute this equation into the other equations: | ( 39 − 2 y − 3 z ) + 3 y + 2 z = 34 3 ( 39 − 2 y − 3 z ) + 2 y + z = 26 | . We can simplify: | y − z = − 5 − 4 y − 8 z = − 91 | . Now, y = z − 5 , so that − 4 ( z − 5 ) − 8 z = − 91 , or − 12 z = − 111 . We find that z = 111 12 = 9.25 . Then y = z − 5 = 4.25 and x = 39 − 2 y − 3 z = 2.75 . Explain why this method is essentially the same as the method discussed in this section; only the bookkeeping is different.
Solution Summary: The author explains the difference between the given method and explain if both the methods are same in the mentioned given example.
Here is another method to solve a system of linear equations: Solve one of the equations for one of the variables, and substitute the result into the other equations.Repeat this process until you run out of variables orequations. Consider the example discussed on page 2:
|
x
+
2
y
+
3
z
=
39
x
+
3
y
+
2
z
=
34
3
x
+
2
y
+
z
=
26
|
.
We can solve the first equation for x:
x
=
39
−
2
y
−
3
z
.
Then we substitute this equation into the other equations:
|
(
39
−
2
y
−
3
z
)
+
3
y
+
2
z
=
34
3
(
39
−
2
y
−
3
z
)
+
2
y
+
z
=
26
|
.
We can simplify:
|
y
−
z
=
−
5
−
4
y
−
8
z
=
−
91
|
.
Now,
y
=
z
−
5
, so that
−
4
(
z
−
5
)
−
8
z
=
−
91
, or
−
12
z
=
−
111
.
We find that
z
=
111
12
=
9.25
. Then
y
=
z
−
5
=
4.25
and
x
=
39
−
2
y
−
3
z
=
2.75
.
Explain why this method is essentially the same as the method discussed in this section; only the bookkeeping is different.
Need a deep-dive on the concept behind this application? Look no further. Learn more about this topic, algebra and related others by exploring similar questions and additional content below.
Solve ANY Optimization Problem in 5 Steps w/ Examples. What are they and How do you solve them?; Author: Ace Tutors;https://www.youtube.com/watch?v=BfOSKc_sncg;License: Standard YouTube License, CC-BY
Types of solution in LPP|Basic|Multiple solution|Unbounded|Infeasible|GTU|Special case of LP problem; Author: Mechanical Engineering Management;https://www.youtube.com/watch?v=F-D2WICq8Sk;License: Standard YouTube License, CC-BY